Extracellular volume fraction using contrast-enhanced CT is useful in differentiating intrahepatic cholangiocellular carcinoma from hepatocellular carcinoma - Honda, T.; Onishi, H.; Fukui, H.; Yano, K.; Kiso, K.; Nakamoto, A.; Tsuboyama, T.; Ota, T.; Tatsumi, M.; Tahara, S.; Kobayashi, S.; Eguchi, H.; et al. (Frontiers in Oncology, 2023)
Objectives To evaluate whether tumor extracellular volume fraction (fECV) on contrast-enhanced computed tomography (CT) aids in differentiation between intrahepatic cholangiocellular carcinoma (ICC) and hepatocellular carcinoma (HCC). Methods In this retrospective study, 113 patients with pathologically confirmed ICC (n = 39) or HCC (n = 74) who had undergone preoperative contrast-enhanced CT were enrolled. Enhancement values of the tumor (Etumor) and aorta (Eaorta) were obtained in the precontrast and equilibrium phase CT images. fECV was calculated using the following equation: fECV [%] = Etumor/Eaorta × (100 – hematocrit [%]). fECV values were compared between the ICC and HCC groups using Welch's t-test. The diagnostic performance of fECV for differentiating ICC and HCC was assessed using receiver-operating characteristic (ROC) analysis. fECV and the CT imaging features of tumors were evaluated by two radiologists. Multivariate logistic regression analysis was performed to identify factors predicting a diagnosis of ICC. Results Mean fECV was significantly higher in ICCs (43.8 ± 13.2%) than in HCCs (31.6 ± 9.0%, p< 0.001). The area under the curve for differentiating ICC from HCC was 0.763 when the cut-off value of fECV was 41.5%. The multivariate analysis identified fECV (unit OR: 1.10; 95% CI: 1.01-1.21; p<0.05), peripheral rim enhancement during the arterial phase (OR: 17.0; 95% CI: 1.29-225; p<0.05), and absence of washout pattern (OR: 235; 95% CI: 14.03-3933; p<0.001) as independent CT features for differentiating between the two tumor types. Conclusions A high value of fECV, peripheral rim enhancement during the arterial phase, and absence of washout pattern were independent factors in the differentiation of ICC from HCC.